Blepharophimosis, eczema, and growth and developmental delay in a young adult: late features of Dubowitz syndrome?. Issue 1 (January 1992) - Lyonnet, S; Schwartz, G; Gatin, G; de Prost, Y; Munnich, A; Le Merrer, M
Abstract : The Dubowitz syndrome is a rare autosomal recessive multiple congenital anomaly/mental retardation syndrome. We report here a case of a young adult presenting with several features consistent with this diagnosis. The differential diagnosis is discussed with respect to the absence of microcephaly and intrauterine growth retardation.